Success Operational Audit and Complexity Internal Control of Digital Machinery Employee Performance Inspectorate - Nur Zeina Maya Sari; Rakhmat Nurdin (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2023)
This study aims to determine the Effect of Operational Audit Success and the Complexity of Internal Control of Digital Machines on Employee Performance at the Inspectorate. The data used is primary data in the form of questionnaires distributed to Bandung City Inspectorate employees. The method used in this research is descriptive and verification method. The population in this study were employees of the Bandung City Inspectorate. Sampling as many as 33 respondents. The type of data used in this research is primary data. This study aims to determine the effect of the Success of Operational Audit and the Complexity of Internal Control of Digital Machines on the performance of employees at the Bandung City Inspectorate. This research was conducted using observational data collection techniques, interviews and questionnaires on Bandung City Inspectorate employees who were processed using SEM-PLS. The results of this study indicate that: (1) Operational Audit success affects employee performance, and (2) Machine Internal Control Complexity Digital has an effect on employee performance.